Moisture tolerant cationic RAFT polymerization of vinyl ethers. Issue 42 (7th September 2022) - Shankel, Shelby L.; Lambert, Tristan H.; Fors, Brett P.
Abstract : Cationic RAFT of vinyl ethers was performed without reagent purification and under ambient conditions by utilizing a PCCP acid initiator with a HBD catalyst. Despite inherent nucleophiles, the system retained high chain end fidelity and modularity. Abstract : Cationic reversible addition–fragmentation chain transfer (RAFT) polymerizations have permitted the controlled polymerization of vinyl ethers and select styrenics with predictable molar masses and easily modified thiocarbonylthio chain ends. However, most cationic RAFT systems require inert reaction conditions with highly purified reagents and low temperatures. Our groups recently developed a living cationic polymerization that does not require these rigorous conditions by utilizing a strong organic acid (pentacarbomethoxycyclopentadiene (PCCP)) and a hydrogen bond donor. By combining our PCCP acid promoted polymerization with a chain transfer agent, we have designed a tolerant cationic RAFT system that can be performed neat, open to the air, and at room temperature. Additionally, this system allows us to utilize catalytic amounts of the PCCP acid to furnish polymers with chain end functionality that can be easily isolated and further manipulated to make functional materials.